The Effect of the Australasian Parliamentary Debate Technique on Students’ Argumentative Speaking Ability - Intan Qomariah; Syauki Syauki; Zaharil Anasy (IJEE (Indonesian Journal of English Education), 2020)
ABSTRACTThe goal of this research was to investigate whether the use of the Australasian Parliamentary Debate had an impact on students’ argumentative speaking ability. The method was quantitative with a quasi-experimental design, and the participants of this research were SMAN 29 Jakarta 10th grade social students in the academic year 2017/2018. They were X IIS 2 as the experimental group and X IIS 3 as the control group, consisting of 32 students for each group. Convenience sampling was used to select the participants for this research, and the data were collected using an oral test. The argumentative speaking rubric was used to assess the students’ argumentative speaking ability in the pre- and post-tests. The results of statistical hypothesis testing, using independent sample t-test, found that the t-value was 2.23 on the significance level of 5 percent (α = 0.05), whereas the t table was 1.99 or tobserve > t table. H0 was therefore rejected and Ha was accepted. This finding shows that the use of the Australasian Parliamentary Debate has a positive effect on students’ ability to speak argumentatively.ABSTRAKTujuan dari penelitian ini adalah untuk menginvestigasi apakah penggunaan the Australalasian Parliamentary Debate memiliki pengaruh positif terhadap kemampuan berbicara argumentatif siswa. Metode yang digunakan adalah kuantitatif dengan quasi-experimental sebagai desain penelitian. Partisipan peneliatian adalah siswa SMAN 29 Jakarta kelas X IPS di tahun akademik 2017/2018. Mereka adalah X IIS 2 sebagai kelas eksperimen dan X IIS 3 sebagai kelas kontrol yang masing-masing kelas terdiri dari 32 siswa. Convenience sampling adalah teknik pengambilan sampel yang digunakan untuk pengumpulan data. Instrumen dalam penelitian ini menggunakan tes lisan dengan rubrik berbicara argumentatif untuk menguji kemampuan argumentasi siswa pada pretest dan posttest. Hasil dari tes hipotesis statistika menggunakan uji T- sampel independen menunjukkan bahwa pada degree of significance 5% % (α = 0.05), tvalue sebesar 2.23 sementara t table sebesar 1.99 atau tobserve > t table. Maka dari itu, H0 ditolak dan Ha diterima. Hal ini membuktikan adanya pengaruh positif penggunaan teknik the Australasian Parliamentary Debate pada kemampuan berbicara argumentatif siswa.  How to Cite: Qomariah, I., Syauki, Anasy, Z., E.F. (2020). The Effect of the Australasian Parliamentary Debate Technique on Students’ Argumentative Speaking Ability. IJEE (Indonesian Journal of English Education), 7(1), 48-62. doi:10.15408/ijee.v7i1.16973